Ambulatory pediatricians: how to bridge the gaps in diagnosis and care coordination for neurodevelopmental disorders in France - Willig, Thiébaut-Noël; Blanc, Jean-Paul; Assathiany, Rémy; Bilbault, Claire; Raffier, Laurent; Werner, Andreas (Frontiers in Pediatrics, 2024)
Introduction and aims: The organization of healthcare pathways for neurodevelopmental disorders (NDD) relies on different levels of expertise depending on the complexity of these disorders. NDDs affect between 8 and 15% of children. Historically, national recommendations and healthcare planning measures were initially devoted to autism spectrum disorders and were gradually extended to Attention deficit hyperactivity disorder (ADHD) and specific learning and development disorders. Private doctors play an increasing role in these pathways at different levels of care due to difficulties in organization, particularly in the health and social sector. The aim of this work was to evaluate the contribution of second-line private doctors in the diagnosis and care of children affected by NDD.